The People’s Revolution of 1921 as a Phenomenon of the Social Transformation of Mongolian Society - Venera V. Kuftareva (Гуманитарный вектор)
The article deals with the phenomenon of the Mongolian People’s Revolution of 1921 and its significance for the social transformations of the Mongolian society. The revolution had unique features that reflected historical features, and, at the same time, had properties similar to other types of sociocultural changes. The people’s revolution of 1921 at the initial stage of its development belonged to the world of ideas, represented a phenomenon that was more speculative, but under the influence of internal and external factors, it acquired empirical features. In the course of deepening social transformations, it gradually turned into a phenomenon and began to represent an exceptional phenomenon, especially in terms of eliminating the feudal system and gaining international recognition. We see the reflection of all these ideas in the writings of many Mongolian and Soviet historians. His Works Academician Bazaryn Shirendyb, Doctor of Historical Scienc, on the topic of revolution are recognized as fundamental. The article reflects the main points of the revolutionary process, their characteristics and significance for the Mongolian people. The tasks of the revolution are touched upon, the democratic transformations of the People’s Government during the period of the formation of people’s power and its role in strengthening the national independence of the country are disclosed in detail. The author of the article used general scientific (analysis, information collection, synthesis, extrapolation) and special methods (comparative, typological, periodization method). Moreover, to understand the sequence of revolutionary events, the historical-genetic method The article deals with the phenomenon of the Mongolian People’s Revolution of 1921 and its significance for the social transformations of the Mongolian society. The revolution had unique features that reflected historical features, and, at the same time, had properties similar to other types of sociocultural changes. The people’s revolution of 1921 at the initial stage of its development belonged to the world of ideas, represented a phenomenon that was more speculative, but under the influence of internal and external factors, it acquired empirical features. In the course of deepening social transformations, it gradually turned into a phenomenon and began to represent an exceptional phenomenon, especially in terms of eliminating the feudal system and gaining international recognition. We see the reflection of all these ideas in the writings of many Mongolian and Soviet historians. His Works Academician Bazaryn Shirendyb, Doctor of Historical Scienc, on the topic of revolution are recognized as fundamental. The article reflects the main points of the revolutionary process, their characteristics and significance for the Mongolian people. The tasks of the revolution are touched upon, the democratic transformations of the People’s Government during the period of the formation of people’s power and its role in strengthening the national independence of the country are disclosed in detail. The author of the article used general scientific (analysis, information collection, synthesis, extrapolation) and special methods (comparative, typological, periodization method). Moreover, to understand the sequence of revolutionary events, the historical-genetic method was used based on the principles of historicism, consistency and reliance on historical sources. The theme of the revolution remains relevant and attracts new researchers. We study the historical path followed by Mongolia in the XX century as an exceptional phenomenon.